Pengaruh Spiritual Emotional Freedom Technique Terhadap Kepatuhan Terapi Penderita Hipertensi - Prihati, Kurniati; Fatmawati, Baiq Ruli; Arifin, Zaenal (Jurnal Ilmiah STIKES Yarsi Mataram, 2022)
Hypertension is a disease with long-term therapy even for life and is sustainable at home, especially with this pandemic condition, it is very necessary for patient compliance in carrying out hypertension therapy on a regular basis. Patient compliance in carrying out therapy can fluctuate. One of the main strategies that can be done to increase compliance is from the patient's perspective by increasing individual confidence. One way that can be used to control psychology is to use the Spiritual Emotional Freedom Technique. The purpose of this study was to determine the effect of SEFT on adherence to therapy in patients with hypertension. The research method used is a quasi-experimental approach with a pretest posttest with control group design. This study uses primary data with a population of 57 people in the working area of the Penimbung Public Health Center with a sample of each control and intervention group of 13 people.data were analyzed bivariately using the paired T-test. There is an effect of Spiritual Emotional Freedom Technique (SEFT) on therapy adherence in patients with hypertension (p = 0.000). The SEFT method can increase patient understanding and awareness in therapy adherence